REKONSTRUKSI TARI SAMBUT SILAMPARI DI KABUPATEN MUSI RAWAS - Stepanus Adi Pratiswa (Institut Seni Indonesia Surakarta, 2014)
The article is meant to describe dance Sambut Silampari in Musi Rawas Residence that previously has afunction as a formal guest welcoming dance, then it is reconstructed through (1) dance digging, (2) dancecompacting, (3) increasing and disseminating the dance works. The dance digging is supposed to reconstructdance that comes from folk dance. It includes the dancer, musician, and dress maker, as well as Musi Rawasartists. The research uses qualitative method in form of descriptive analysis. The discussion scope includes1) how the process of dance Sambut Silampari reconstruction, 2) how the form resulted from the reconstruction,and 3) whatever factors that support the reconstruction. Data analysis is done in every element founded. Thedata collected from library study, observation, and interview is analyzed using the method of descriptiveanalysis and qualitatively in condition with the main problem. The concept used in the reconstruction of danceSambut Silampari is the concept of form in dance study: text and context by giving innovation to concept oftourism art that is brief, compacted, interesting, and commercial. Based on the concept, then, dance SambutSilampari can be the asset of performing arts in Musi Rawas Residence.Keywords: reconstruction, dance Sambut Silampari, tourism art